Spontaneous and Procedural Plaque Embolisation in Native Coronary Arteries: Pathophysiology, Diagnosis, and Prevention - Giovanni Luigi De Maria; Niket Patel; George Kassimis; Adrian P. Banning (Scientifica)
The detachment of atherothrombotic material from the atherosclerotic coronary plaque and downstream embolisation is an underrecognized phenomenon and it causes different degrees of impairment of the coronary microcirculation. During treatment of obstructive atherosclerotic plaque by percutaneous coronary intervention (PCI) distal embolisation (DE) is considered to be inevitable and it is associated with potential clinical and prognostic implications. This review aims to assess the main aspects of both spontaneous and procedural DE, analyze their different pathophysiology, provide specific insights on the main diagnostic tools for their identification, and finally focus on the main strategies for their treatment and prevention.